2011
DOI: 10.1111/j.1467-8624.2011.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Dual Language Exposure That Influence 2-Year-Olds’ Bilingual Proficiency

Abstract: The mothers of 29 Spanish-English bilingual 25-month-olds kept diary records of their children's dual language exposure and provided information on their children's English and Spanish language development using the MacArthur-Bates inventories. Relative amount of exposure predicted language outcomes in English and Spanish. In addition, the number of different speakers from whom the children heard English and the percent of their English input that was provided by native speakers were unique sources of variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
465
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 521 publications
(520 citation statements)
references
References 32 publications
45
465
3
7
Order By: Relevance
“…The present studies found that English input from native English speakers is more useful to children's language growth than English input from late learners of English Place & Hoff, 2011. Work in progress is examining properties of native and non-native child-directed English to ask why this should be the case.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The present studies found that English input from native English speakers is more useful to children's language growth than English input from late learners of English Place & Hoff, 2011. Work in progress is examining properties of native and non-native child-directed English to ask why this should be the case.…”
Section: Resultsmentioning
confidence: 70%
“…In other work we have found that the percentage of bilingual children's English exposure that is provided by native speakers predicts the children's English skill, over and above the effects of how much English the children hear (Place & Hoff, 2011; English use in the home is strongly related to children's English skills among bilingual children who have one native English-speaking parent and English use at home is only weakly related to children's English skills among children with two native Spanish-speaking parents .…”
Section: Hoff Bilingual Vs Monolingual Developmentmentioning
confidence: 71%
See 2 more Smart Citations
“…For example, in L2 education it is important to consider from whom children are learning the L2. Place and Hoff [56] found that hearing English from different speakers and the amount of English input provided by native speakers is critical for learning English as L2. Another notable difference between L1 and L2 learning is that children may rely on their L1 when learning an L2 (e.g., [75]).…”
Section: Second Language Learningmentioning
confidence: 99%